2014
DOI: 10.4172/2168-9857.1000135
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for Overall Survival of Japanese Patients with Bone Metastatic Prostate Cancer

Abstract: Objective: We analyzed the relationship between prostate cancer outcome and pretreatment clinical factors, and developed a prognostic nomogram for Overall Survival (OS) of patients with bone metastasis. Methods:Beginning in 1993 to 2011, 463 consecutive prostate cancer patients with bone metastasis were treated. Data sets from 361 patients were used to develop the nomogram (training data), and data sets of 102 patients were used for validation of the nomogram (validation data). Using the external validation da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Because patients with mHNPC have various survival risks [21], survival risk classifications before treatment may provide useful information for selecting treatment strategies. Previously, we reported that mHNPC patients with high LMW-PTP expression had shorter overall survival than did patients with low expression [8].…”
Section: Lmw-ptp Expression and Survivalmentioning
confidence: 99%
“…Because patients with mHNPC have various survival risks [21], survival risk classifications before treatment may provide useful information for selecting treatment strategies. Previously, we reported that mHNPC patients with high LMW-PTP expression had shorter overall survival than did patients with low expression [8].…”
Section: Lmw-ptp Expression and Survivalmentioning
confidence: 99%
“…15 In another series, age was further confirmed to be an independent prognostic factor for OS in men with mPCa, and when it was incorporated into a pretreatment prognostic nomogram, age had reasonable discriminatory performance. 16 However, such studies were performed before the development and approval of many life-prolonging therapies for metastatic castration-resistant prostate cancer (mCRPC), including drugs targeting the androgen receptor signaling axis (abiraterone and enzalutamide), chemotherapy (docetaxel, cabazitaxel), and radiopharmaceuticals (radium-223). More recently, standards of care have changed such that ADT and docetaxel or ADT and abiraterone are now used earlier in the mHSPC setting, and this further improves survival.…”
Section: Introductionmentioning
confidence: 99%
“…Their nomogram showed that a lower PSA level contributed to higher total points, therefore there was a worse prognosis. 20 We analyzed PSA as a continuous variable, which is similar to the Miyoshi et al nomogram. The J-CAPRA database supports the present findings.…”
Section: Discussionmentioning
confidence: 99%